Effects of catalyst agglomerate shape in polymer electrolyte fuel cells investigated by a multi-scale modelling framework. (1st March 2017) - Ismail, M.S.; Ingham, D.B.; Ma, L.; Hughes, K.J.; Pourkashanian, M.
Abstract: A multi-scale modelling framework is developed for the PEFC cathode electrode. Unlike the conventional agglomerate model, the effects of the microstructure of the agglomerate are numerically coupled to the fuel cell-scale model in this framework. This is performed through solving the agglomerate-scale model first and subsequently extracting and using the data required to generate the performance curves in the fuel cell-scale model. This enables one to freely investigate the structure of the agglomerate without being limited to the only three agglomerate shapes that can be investigated using the conventional agglomerate model: spheres, long cylinders with sealed ends and long slabs with sealed ends. The numerical studies conducted in this work using the developed framework have revealed that the performance of the cathode electrode is highly sensitive to the specific surface area of the agglomerate if the size of the latter is relatively large, i.e. of the order of 1000 nm. Namely, the maximum reported current density has increased by about 60% when changing from the 'large' spherical agglomerate to the 'large' cylindrical agglomerate. Also, it has been shown that a slight change in the structure of the agglomerate may significantly improve the fuel cell performance. Graphical abstract: The interpolation plot is extracted from the agglomerate-scale model and used in the fuel cell-scale model to compute the local current density of the electrode. The above interpolation plot is for a spherical agglomerate with a radius of 1000 nm. Highlights: A multi-scale modelling framework for PEFC cathode electrodes has been developed. With this framework, the structure of the catalyst agglomerate is freely investigated. The fuel cell performance is almost insensitive to the shape of 'small' agglomerates (<200 nm). The performance becomes more sensitive to the shape as the agglomerate size increases. The larger is the specific surface area of the agglomerate, the better is the performance.